Re-Engineering Faith Based Birth Homes (FBBH) and Faith Based Birth Attendants (FBBA) as Complimentary Ante-Natal Care in Ibadan, Nigeria - Oke, Ruth Oluwakemi; Kehinde, Fabunmi Samuel (International Journal of Research in Interdisciplinary Studies, 2025)
Childbirth is an important aspect of the human life. In fact, the world would have gone to extinction if there has not been procreation. The blessing to increase, populate and dominate the earth was the key to procreation. However, in spite of this divine blessing, there are challenges be-devilling pregnancy and childbirth for women of childbearing age. The travail to access antenatal care and the cost implication which is enormous especially within Ibadan Metropolis and its environs is the focus of this research. Government health institutions (GHI) are not able to serve all antenatal care, makes this research plausible by looking into the activities of Faith Based Birth Homes (FBBH)and Faith Based Birth Attendants (FBBA) as alternative to the Government health institutions with a few of re-engineering them for optimal performance. The research is premised on Stages of Change Model which identified five stages of change in human behaviour. Methodology adopted for this research is ethnographic survey, which includes Focused Group Discussion and Participatory observation. It was discovered that patronage of FBBH and FBBA by pregnant women within the Christian faith community and the society at large were high owing to a number of factors like serene environment, reduced cost implications, closeness to the women, good infrastructure and humane disposition. There is need for government intervention on FBBH and FBBA to better serve the needs of the people.